2009
DOI: 10.5194/npg-16-631-2009
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and transport of ions in turbulent current sheets: formation of non-maxwelian energy distribution

Abstract: Abstract. The paper is devoted to particle acceleration in turbulent current sheet (CS). Our results show that the mechanism of CS particle interaction with electromagnetic turbulence can explain the formation of power law energy distributions. We study the ratio between adiabatic acceleration of particles in electric field in the presence of stationary turbulence and acceleration due to electric field in the case of dynamic turbulence. The correlation between average energy gained by particles and average par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 69 publications
4
21
0
Order By: Relevance
“…Thus, the waves may play some roles in the time evolution of the DFs. The ion fluxes enhancements around DFs may be caused by the low wave activities with a frequency comparable to the local ion cyclotron frequency (Artemyev et al, 2009;Nosé et al, 2010;Ono et al, 2009). We also observed quasi-parallel whistler waves before, during and after the DFs.…”
Section: Wave Analysismentioning
confidence: 54%
“…Thus, the waves may play some roles in the time evolution of the DFs. The ion fluxes enhancements around DFs may be caused by the low wave activities with a frequency comparable to the local ion cyclotron frequency (Artemyev et al, 2009;Nosé et al, 2010;Ono et al, 2009). We also observed quasi-parallel whistler waves before, during and after the DFs.…”
Section: Wave Analysismentioning
confidence: 54%
“…Moreover all beams of this type are characterized by velocity distribution functions rather wide in parallel energies: V D /V T ≥ 1 (contrary to Type-I beams which have V D /V T 1 and energies below the typical value of the potential drop across the tail). Artemyev et al (2009) demonstrated that electromagnetic turbulence could play a role in the process of particle izotropization in the CS, as well as in their acceleration by any inductive electric fields. Therefore Type-II ion beams formation could also be described by a model of particle interaction with the turbulent electromagnetic fields near the X-line.…”
Section: Modeling Of the Formation Of Type-ii Ion Distribution Functimentioning
confidence: 98%
“…Magnetic turbulence developing in the vicinity of the magnetic reconnection region could also become a source of inductive electric fields. Its role in ion acceleration was discussed in detail by Milovanov and Zelenyi (2001) and Artemyev et al (2009). Finally, large electrostatic oscillations arising near the reconnection region could also contribute to the acceleration of non-adiabatic particles (Hoshino et al 2000).…”
Section: Brief Introduction To Ion Non-adiabatic Acceleration In the mentioning
confidence: 97%
“…According to the numerical modeling, ion interaction with such a turbulent field should result in the particle acceleration in the vicinity of the neutral plane Perri et al, 2009;Greco et al, 2010). The natural limitation of possible energy gain corresponds to the particles escaping from the turbulent current sheet due to the fast motion along the curved magneticfield lines (Artemyev et al, 2009b;Perri et al, 2011). In this case, some specific properties of electromagnetic turbulence (like a spatial intermittency) can increase the efficiency of the acceleration .…”
Section: A V Artemyev Et Al: High-energy Ion Spectra In the Magnetmentioning
confidence: 99%